Another approach for theoretical recognition method (II) - Sugiyama, Shigeki (2010 5th IEEE Conference on Industrial Electronics and Applications, 2010)
We speak languages sometimes fast and sometimes slowly. We sometimes even stop speaking suddenly, and change the topic and start speaking about another subject. And also, we sometimes speak to a person whom we have met for the first time. Even in these situations, we can happily understand one another what we are talking about even though the speech signals wave forms are independent one another. But if we apply some of today's speech analysis methods in these situations mentioned above, we may totally get different answers or even cannot apply those methods. And what is worse, application of those methods are quite difficult and it is not understandable what will be the causes in a practice situation. So on this paper, I have tried to study a simple method which can apply to in the difficult situations mentioned above by using Vector Analysis Method and Back Propagation Neural Networks Method, which mainly focuses on "Word feedback and Sentence feedback".